2018
DOI: 10.1093/eurheartj/ehy043
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac diagnostic work-up of ischaemic stroke

Abstract: Cardioembolic sources account for 20-30% of ischaemic strokes and are important to identify considering their prognostic and therapeutic implications. During the past years, new developments have been made in the cardiac diagnostic evaluation and management of patients with ischaemic stroke, especially regarding strokes of unknown aetiology. These recent advances have had a major impact on our understanding of embolic strokes, their diagnostic work-up, and clinical management. Herein, we propose a cardiac diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 54 publications
0
19
0
1
Order By: Relevance
“…Another marked difference in our population compared to other studies is the high prevalence of cardioembolic strokes in the older group, which accounted for 43.3% of all ischaemic strokes, and low prevalence of cryptogenic stroke (18.1%). Recent data estimate that cardioembolic strokes account for 20–30% and cryptogenic mechanisms are responsible for 30–40% of ischaemic strokes across all ages . However, using extended cardiac monitoring, up to 9.2% of cryptogenic strokes can be re‐classified as due to atrial fibrillation, a major cause of cardioembolism .…”
Section: Discussionmentioning
confidence: 99%
“…Another marked difference in our population compared to other studies is the high prevalence of cardioembolic strokes in the older group, which accounted for 43.3% of all ischaemic strokes, and low prevalence of cryptogenic stroke (18.1%). Recent data estimate that cardioembolic strokes account for 20–30% and cryptogenic mechanisms are responsible for 30–40% of ischaemic strokes across all ages . However, using extended cardiac monitoring, up to 9.2% of cryptogenic strokes can be re‐classified as due to atrial fibrillation, a major cause of cardioembolism .…”
Section: Discussionmentioning
confidence: 99%
“…Despite extensive etiologic investigations, no specific cause has been found in 30–40% of ischemic stroke patients [5]. In the literature, it has been reported that the etiology of these patients with strokes of undetermined origin, or otherwise referred to as "cryptogenic strokes," is likely to be thromboembolic, and the emboli are mostly of cardiac origin [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Cardioembolic stroke has a worse prognosis than other etiological factors in terms of mortality, disability, and recurrence [17]. Although many cardioembolic risk factors that result in ischemic stroke are known, the most common cardioembolic stroke cause in daily clinical practice is atrial fibrillation [5,17]. Paroxysmal or chronic atrial fibrillation is known as a well-defined etiologic cause of ischemic stroke, and the risk of stroke can be reduced by appropriate anticoagulant therapy with both primary and secondary prevention [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Medium/low-risk sources included mitral annular calcification, aortic valve calcification, patent foramen ovale, 11 atrial septal aneurysm, and presence of LV aneurysm without thrombus. 28 In addition, filling defects suspected to be an intracardiac thrombus, but lacking an oval shape or lower attenuation, were noted as a medium/low-risk source. 26,27 Outcome assessments…”
Section: Image Analysismentioning
confidence: 99%